Polymer modified asphalt special for bridge floor and preparation method of polymer modified asphalt

By using bridge deck-specific polymer modified asphalt in bridge deck materials, the problem of insufficient durability and safety of traditional asphalt concrete in complex environments is solved, higher adhesion and durability are achieved, and the overall performance of bridge deck materials is improved.

CN119708871APending Publication Date: 2025-03-28HAIYUN (HAINAN) MATERIALS TECHNOLOGY CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510076725.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The traditional bridge deck material asphalt concrete has poor durability and safety in environments such as high temperature, low temperature, ultraviolet radiation, chemical corrosion and vehicle overload, and cannot meet the needs of modern bridge construction.

Method used

The adhesion and durability of the asphalt are improved by specific preparation methods, including matrix asphalt, aromatic oil, linear SBS, SBR, sodium dodecyl benzenesulfonate, nanocarbon black and stabilizer.

Benefits of technology

It improves the adhesion between modified asphalt and stone, enhances the durability and safety of bridge deck materials, and reduces material costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of road engineering asphalt, and particularly relates to special polymer modified asphalt for a bridge floor and a preparation method of the special polymer modified asphalt. The modified asphalt is prepared from the following components in parts by weight: 85 to 100 parts of matrix asphalt, 2.0 to 4.0 parts of aromatic hydrocarbon oil, 3.0 to 4.5 parts of SBS (Styrene Butadiene Styrene), 1.0 to 1.5 parts of SBR (Styrene Butadiene Rubber), 0.1 to 0.5 part of sodium dodecyl benzene sulfonate, 0.1 to 0.2 part of nano carbon black and 0.2 to 0.4 part of stabilizer. According to the technical scheme, the SBS modifier and the SBR modifier are complementary in advantages, the adhesion of the modified asphalt is improved, the road surface driving safety is improved, the interfacial tension of the modifier and the asphalt is reduced through the preferable surfactant, the adhesion of the modified asphalt and stone is enhanced, the stabilizer is optimized, and the stabilizer is matched with the nano carbon black in a specific proportion, so that the comprehensive performance of the asphalt is improved. The solubility parameter difference between the modifier and the asphalt is optimally reduced, and the durability and the safety of the bridge deck asphalt are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering asphalt, and specifically relates to a special polymer modified asphalt for bridge deck and a preparation method thereof. Background Art

[0002] With the development of society and the increase in traffic volume, bridges, as an important transportation infrastructure, are increasing in number and span. However, the environment in which bridges are located is complex and is often affected by natural environmental factors and human factors, such as high temperature, low temperature, ultraviolet radiation, chemical corrosion, vehicle overload, etc. These factors will damage the structure and materials of bridges, resulting in a decrease in the durability and safety of bridges. Therefore, improving the durability and safety of bridges has become an urgent problem to be solved. In bridge construction, the selection of bridge deck materials is one of the key factors. Traditional bridge deck materials are mainly asphalt concrete, but due to some shortcomings of asphalt concrete, such as poor fatigue resistance and poor durability, it can no longer meet the needs of modern bridge construction. Therefore, polymer modified asphalt is used to improve the durability and safety of bridge deck materials. Due to the particularity of the bridge structure, the bridge deck asphalt needs to have good adhesion to ensure close bonding with the bridge deck base to prevent peeling and falling off, which affects the driving safety of the bridge deck. Summary of the invention

[0003] The purpose of the present invention is to provide a special polymer modified asphalt for bridge deck and a preparation method thereof, so as to improve the adhesion with stone materials, improve the durability and safety of asphalt pavement, and solve the problems existing in the above-mentioned background technology.

[0004] To achieve the above objectives, this application is implemented through the following technical solutions:

[0005] A polymer modified asphalt specially used for bridge decks, comprising the following components in parts by weight:

[0006] 85-100 parts of base asphalt;

[0007] Aromatic oil 2.0-4.0 parts;

[0008] SBS 3.0-4.5 parts;

[0009] SBR 1.0-1.5 parts;

[0010] Sodium dodecylbenzenesulfonate 0.1-0.5 parts;

[0011] Nano carbon black 0.1-0.2 parts;

[0012] Stabilizer 0.2-0.4 parts.

[0013] Furthermore, the SBS is a linear SBS with a block ratio of 30:70, and a molecular weight of the SBS is 100,000-150,000.

[0014] Furthermore, the SBR is styrene-butadiene rubber.

[0015] Furthermore, the weight ratio of SBS to SBR is 2.6:1.

[0016] Furthermore, the particle size of the nano carbon black is 50-100 nm.

[0017] Furthermore, the stabilizer is one or more of sulfur, calcium oxide or silicon oxide.

[0018] A method for preparing polymer-modified asphalt for bridge decks, comprising the following steps:

[0019] S1. Shear the base asphalt, SBS and SBR at 170-180℃ for 30-50min.

[0020] S2, adding aromatic oil and sodium dodecylbenzene sulfonate to the asphalt sheared in step S1, and swelling the asphalt at 175-180° C. for 40 min-60 min;

[0021] S3. Add nano carbon black and stabilizer to the swollen asphalt, and develop it at 175-180° C. for 120 min-180 min to obtain polymer modified asphalt specially used for bridge deck.

[0022] Furthermore, in step S1, the base asphalt and SBR are sheared at 170-180°C for 20-30 minutes, and then SBS is added and sheared for another 10-20 minutes.

[0023] Furthermore, step S1 further includes shearing the base asphalt and SBR at 170-180° C. for 20-30 min, then adding SBS in an amount equal to that of SBR and continuing shearing for 10-20 min, and adding the remaining SBS simultaneously with the aromatic oil and sodium dodecylbenzene sulfonate in step S2.

[0024] The beneficial effects of the present invention are:

[0025] 1. The present invention optimizes the modifier and adopts SBS and SBR modifiers to complement each other, thereby improving the adhesion of modified asphalt and improving road driving safety. In particular, the present invention designs the weight ratio of the modifier SBS to SBR to be 2.6:1. Compared with other asphalts that use SBS and SBR as modifiers at the same time and in other proportions, the adhesion is significantly improved, especially in actual use, between the stone at the production site and the asphalt produced by this technology.

[0026] 2. The present invention optimizes surfactants to reduce the interfacial tension between the modifier and asphalt. Sodium dodecylbenzene sulfonate improves the compatibility between asphalt and the modifier and enhances the adhesion between the modified asphalt and the stone. The technical solution also improves the effect of surfactants on reducing the interfacial tension between the modifier and asphalt according to a specific preparation method, especially adding SBS and SBR separately and adding SBS in batches, which is significantly better than the effect of adding SBS and SBR at the same time.

[0027] 3. The present invention optimizes the modified asphalt stabilizer component, uses nano carbon black and stabilizer in combination, and the usage ratio of stabilizer to nano carbon black is 2:1, which achieves the optimal reduction of the solubility parameter difference between the modifier and asphalt, and improves the durability and safety of bridge deck asphalt.

[0028] 4. The modifier used in the present invention is cheap, which reduces the cost of bridge deck asphalt materials. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail below in conjunction with embodiments. The following embodiments are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.

[0030] The technical solution of the present invention is described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present application provides a polymer-modified asphalt specially used for bridge decks, wherein the base asphalt in its components is the base asphalt in the asphalt conventionally used for bridge decks, that is, the technical solution of the present application is a modified design based on the conventional base asphalt.

[0032] The base asphalt of the present application is No. 70 road petroleum asphalt, with a needle penetration of 60-80dmm, an asphalt colloid instability index of less than 0.4, and an elongation of ≥7cm after aging.

[0033] The raw materials involved in this application can all be obtained through commercial channels.

[0034] The present application provides a special polymer modified asphalt for bridge decks, which is composed of the following components in parts by weight:

[0035] 85-100 parts of base asphalt;

[0036] Aromatic oil 2.0-4.0 parts;

[0037] SBS 3.0-4.5 parts;

[0038] SBR 1.0-1.5 parts;

[0039] Sodium dodecylbenzenesulfonate 0.1-0.5 parts;

[0040] Nano carbon black 0.1-0.2 parts;

[0041] Stabilizer 0.2-0.4 parts.

[0042] In the present application, the styrene-butadiene-styrene block copolymer SBS is a linear SBS with a block ratio of 30:70, and the molecular weight of the SBS is 100,000-150,000.

[0043] In the present application, styrene butadiene rubber SBR refers to styrene butadiene rubber.

[0044] In the present application, the weight ratio of SBS to SBR is 2.6:1. Modified asphalt can also be obtained for other usage ratios, but they cannot achieve the technical effect of the present application. Therefore, the present technical solution only protects this ratio relationship.

[0045] In the present application, the particle size of nano carbon black is 50-100 nm, which reduces the interfacial tension between asphalt and the modifier and improves the adhesion of the modified asphalt.

[0046] In the present application, the stabilizer is one or more of sulfur, calcium oxide or silicon oxide. It is preferred to use a single stabilizer. Two or three stabilizers can also be used in the present technical solution, but it is not the best effect. In the present application, the best weight ratio of the stabilizer to the nano carbon black is 2:1.

[0047] In the present application, a method for preparing polymer-modified asphalt for bridge deck is also provided, which adopts the following steps:

[0048] S1. Shear the base asphalt, SBS and SBR at 170-180°C for 30-50 minutes;

[0049] S2, adding aromatic oil and sodium dodecylbenzene sulfonate to the asphalt sheared in step S1, and swelling the asphalt at 175-180°C for 40-60 minutes;

[0050] S3. Add nano carbon black and stabilizer to the swollen asphalt, and develop it at 175-180° C. for 120 min to 180 min to obtain polymer modified asphalt specially used for bridge deck.

[0051] In the present application, in step S1, the method of simultaneously putting the base asphalt, SBS and SBR into the reactor is not adopted, but the following method is adopted: the base asphalt and SBR are sheared at 170-180°C for 20-30 minutes, and then SBS is added and shearing is continued for 10-20 minutes.

[0052] In the present application, in step S1, the method of simultaneously putting the base asphalt, SBS and SBR into the reactor is not adopted for preparation, but the following method is adopted: the base asphalt and SBR are sheared at 170-180°C for 20-30 minutes, and then SBS equal to the SBR is added and shearing is continued for 10-20 minutes, and the remaining SBS is added simultaneously with the aromatic oil and sodium dodecylbenzene sulfonate in step S2.

[0053] The performance indexes of the polymer modified asphalt for bridge decks prepared by the above two feeding methods are better than those prepared by simultaneously feeding base asphalt, SBS and SBR into the reactor. It should be the method of adding SBS and SBR separately and adding SBS in batches, which improves the effect of surfactant on reducing the interfacial tension between the modifier and asphalt, which is significantly better than the effect of adding SBS and SBR simultaneously.

[0054] Example 1

[0055] 500g of base asphalt was added with 13g of modifier 791H SBS and 5g of SBR for shearing at a shearing temperature of 175°C, a shearing time of 40min, and a rotation speed of 4000 r / min. After shearing, the obtained sample was transferred to a temperature-controlled heating jacket, and 15g of aromatic oil and 1.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175°C. After swelling, 1.6g of stabilizer and 0.8g of nano carbon black were added and stirred for 120min. The temperature was controlled at 175°C to obtain polymer modified asphalt P1 for bridge decks.

[0056] Example 2

[0057] 500g of base asphalt was sheared with 5g of SBR modifier at a shear temperature of 175°C, a rotation speed of 4000 r / min, and a shear time of 30min. 13g of 791H SBS modifier was added, and shearing was continued at a shear temperature of 175°C for 10min. After the shearing was completed, the sample was transferred to a temperature-controlled heating jacket, and 15g of aromatic oil and 1.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175°C. After the swelling was completed, 1.6g of stabilizer and 0.8g of nano carbon black were added, stirred and developed for 120min, and the temperature was controlled at 175°C to obtain polymer modified asphalt P2 for bridge decks.

[0058] Example 3

[0059] 500g of base asphalt was added with 5g of modifier SBR for shearing at a shear temperature of 175℃, a rotation speed of 4000 r / min, and a shearing time of 30min. 5g of modifier 791H SBS was added, and shearing was continued at a shear temperature of 175℃ for 10min. After the shearing was completed, the obtained sample was transferred to a temperature-controlled heating jacket, and the remaining SBS 8g, 15g of aromatic oil, and 1.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175℃. After the swelling was completed, 1.6g of stabilizer and 0.8g of nano carbon black were added and stirred for 120min. The temperature was controlled at 175℃ to obtain polymer modified asphalt P3 for bridge deck.

[0060] Example 4

[0061] 500g of base asphalt was added with 19.5g of modifier 791H SBS and 7.5g of SBR for shearing at a shearing temperature of 175°C, a shearing time of 40min, and a rotation speed of 4000 r / min. After shearing, the obtained sample was transferred to a temperature-controlled heating jacket, and 20g of aromatic oil and 2.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175°C. After swelling, 2.0g of stabilizer and 1.0g of nano carbon black were added and stirred for 120min. The temperature was controlled at 175°C to obtain polymer modified asphalt P4 for bridge decks.

[0062] Example 5

[0063] 500g of base asphalt was added with 7.5g of modifier SBR for shearing at a shear temperature of 175°C, a rotation speed of 4000 r / min, and a shearing time of 30min. Then 19.5g of modifier 791H SBS was added, and shearing was continued at a shear temperature of 175°C for 10min. After the shearing was completed, the obtained sample was transferred to a temperature-controlled heating jacket, and 20g of aromatic oil and 2.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175°C. After the swelling was completed, 2.0g of stabilizer and 1.0g of nano carbon black were added and stirred for 120min. The temperature was controlled at 175°C to obtain polymer modified asphalt P5 for bridge decks.

[0064] Example 6

[0065] 500g of base asphalt was added with 7.5g of modifier SBR for shearing at a shear temperature of 175℃, a rotation speed of 4000 r / min, and a shearing time of 30min. 7.5g of modifier 791H SBS was added, and shearing was continued at a shear temperature of 175℃ for 10min. After the shearing was completed, the obtained sample was transferred to a temperature-controlled heating jacket, and the remaining 12g of SBS, 20g of aromatic oil, and 2.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min, and the temperature was controlled at 175℃. After the swelling was completed, 2.0g of stabilizer and 1.0g of nano carbon black were added and stirred for 120min. The temperature was controlled at 175℃ to obtain polymer modified asphalt P6 for bridge deck.

[0066] Comparative Example 1

[0067] 500 g of base asphalt was added with 20 g of modifier 791H SBS for shearing at a shearing temperature of 175 °C, a shearing time of 40 min, and a rotation speed of 4000 r / min. After shearing, the obtained sample was transferred to a temperature-controlled heating jacket, and 15 g of aromatic oil was added for swelling. The swelling time was 50 min, and the temperature was controlled at 175 °C. After swelling, a stabilizer was added and stirred for 120 min, and the temperature was controlled at 175 °C to obtain bridge deck asphalt D1.

[0068] Comparative Example 2

[0069] 500g of base asphalt was added with 15g of modifier 791H SBS and 5g of SBR for shearing at a shearing temperature of 175°C, a shearing time of 40min, and a rotation speed of 4000 r / min. After shearing, the obtained sample was transferred to a temperature-controlled heating jacket, and 15g of aromatic oil was added for swelling. The swelling time was 50min and the temperature was controlled at 175°C. After swelling, a stabilizer was added and stirred for 120min. The temperature was controlled at 175°C to obtain bridge deck asphalt D2.

[0070] Comparative Example 3

[0071] 500g of base asphalt was added with 15g of modifier 791H SBS and 5g of SBR for shearing at a shearing temperature of 175°C, a shearing time of 40min, and a rotation speed of 4000 r / min. After shearing, the obtained sample was transferred to a temperature-controlled heating jacket, and 15g of aromatic oil and 1.5g of sodium dodecylbenzene sulfonate were added for swelling. The swelling time was 50min and the temperature was controlled at 175°C. After swelling, a stabilizer was added and stirred for 120min. The temperature was controlled at 175°C to obtain bridge deck asphalt D3.

[0072] The test results of bridge deck asphalt of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1:

[0073] Table 1 Modified asphalt indexes of Examples 1-6 and Comparative Examples 1-3 Test items D1 D2 D3 P1 P2 P3 P4 P5 P6 Test methods Needle penetration (25℃, 100g, 5s) / 0.1mm 54 55 54 54 54 54 54.5 54.5 54.5 T 0604 Elongation / cm 32 40 41 43 44 44.2 44.3 44.6 44.6 T 0605 Segregation / ℃ 15.2 16.0 2.0 0.2 0.2 0.2 0.24 0.24 0.24 T 0611 Viscosity / Nm 14 20 22 25 26.2 26.1 25.3 26.1 25.9 T 0624 Cohesion / N 56 62 63 81 82.1 81.9 80.4 81.3 81.2 /

[0074] The performance of the bridge asphalt pavement of Examples 1-6 and Comparative Examples 1-3 is shown in Table 2: Test items D1 D2 D3 P1 P2 P3 P4 P5 P6 Freeze-thaw splitting test, freeze-thaw splitting strength ratio (%) 81.0 83.2 85.9 88.2 88.4 88.3 88.3 88.6 88.5 Marshall test after immersion in water, residual stability after immersion in water (%) 85.3 86.4 87.1 89.7 89.9 90.0 89.8 90.1 89.9

[0075] It can be seen from the above table: through the modified asphalt indicators of Comparative Examples 1-3 and Examples 1-6 in Table 1, Examples 1-6 are compared with Comparative Examples 1, Comparative Example 2, and Comparative Example 3. The segregation index is smaller, indicating that the modifier and asphalt in the modified asphalt of Examples 1-6 have better properties, and the viscosity and cohesion are larger, indicating that the molecular bond force of the modified asphalt is stronger, and the viscosity of the asphalt and the aggregate is stronger. Examples 2 and 3 are compared with Example 1, and Examples 5 and 6 are compared with Example 4. It is shown that the performance of different preparation processes is different under the same composition, and the performance of Examples 2 and 3 of the present application is better than that of Example 1, and the performance of Examples 5 and 6 is better than that of Example 4.

[0076] In Table 2, the road performance has a relatively large freeze-thaw splitting strength and a relatively large residual stability after immersion in water, which indicates that the road performance exhibits a good ability to resist water damage, a strong pavement durability, and a good fatigue resistance.

[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polymer-modified asphalt for bridge decks, characterized in that: The components are as follows by weight: 85-100 parts of base asphalt; Aromatic oil 2.0-4.0 parts; SBS 3.0-4.5 parts; SBR 1.0-1.5 parts; Sodium dodecylbenzenesulfonate 0.1-0.5 parts; Nano carbon black 0.1-0.2 parts; Stabilizer 0.2-0.4 parts.

2. The polymer-modified asphalt for bridge deck according to claim 1, characterized in that: The SBS is a linear SBS with a block ratio of 30:70 and a molecular weight of 100,000-150,000.

3. The polymer-modified asphalt for bridge deck according to claim 1, characterized in that: The SBR is styrene-butadiene rubber.

4. The polymer-modified asphalt for bridge deck according to claim 1, characterized in that: The weight ratio of the SBS to the SBR is 2.6:

1.

5. The polymer-modified asphalt for bridge deck according to claim 1, characterized in that: The particle size of the nano carbon black is 50-100 nm.

6. The polymer-modified asphalt for bridge deck according to claim 1, characterized in that: The stabilizer is one or more of sulfur, calcium oxide or silicon oxide.

7. A method for preparing polymer-modified asphalt for bridge decks as claimed in any one of claims 1 to 6, characterized in that: Use the following steps: S1. Shear the base asphalt, SBS and SBR at 170-180℃ for 30-50min. S2, adding aromatic oil and sodium dodecylbenzene sulfonate to the asphalt sheared in step S1, and swelling the asphalt at 175-180° C. for 40 min-60 min; S3. Add nano carbon black and stabilizer to the swollen asphalt, and develop it at 175-180° C. for 120 min-180 min to obtain polymer modified asphalt specially used for bridge deck.

8. The method for preparing polymer-modified asphalt for bridge deck according to claim 7, characterized in that: Step S1 also includes shearing the base asphalt and SBR at 170-180° C. for 20-30 minutes, and then adding SBS and continuing shearing for 10-20 minutes.

9. The method for preparing polymer-modified asphalt for bridge deck according to claim 7, characterized in that: Step S1 also includes shearing the base asphalt and SBR at 170-180° C. for 20-30 minutes, then adding SBS equal to the SBR and continuing shearing for 10-20 minutes, and adding the remaining SBS together with the aromatic oil and sodium dodecylbenzene sulfonate in step S2.